2022
DOI: 10.1111/jocs.17126
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive versus conventional aortic valve replacement: The network meta‐analysis

Abstract: Background Outcome comparisons after surgical aortic valve replacement (SAVR) with minimally invasive approaches including mini‐sternotomy (MS) and right mini‐thoracotomy (RMT) and full sternotomy (FS) have been conflicting. Furthermore, the synthesis of mid‐term mortality has not been performed. Methods MEDLINE and EMBASE were searched through April 2022 to identify propensity score matched (PSM) studies or randomized controlled trial (RCT) which compared outcomes following SAVR among three incisional approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…In terms of quality of life, results were inconsistently reported, but ranged between not statistically different, to MICS being favorable over full sternotomy. The results were demonstrated for both the mini-sternotomy approach and the right anterior thoracotomy approach when each were compared to full sternotomy, as reported by Ogami et al (meta-analysis) and Stolinski et al (propensity score matched analysis), respectively [26,27]. Likewise, a best evidence analysis review concluded that both mini-sternotomy and right anterior thoracotomy, despite longer operative times, provide similar short term outcomes compared to full sternotomy, with reduced hospital LOS [28].…”
Section: Minimally Invasive Cardiac Surgery – Recent Reviews and Meta...mentioning
confidence: 70%
“…In terms of quality of life, results were inconsistently reported, but ranged between not statistically different, to MICS being favorable over full sternotomy. The results were demonstrated for both the mini-sternotomy approach and the right anterior thoracotomy approach when each were compared to full sternotomy, as reported by Ogami et al (meta-analysis) and Stolinski et al (propensity score matched analysis), respectively [26,27]. Likewise, a best evidence analysis review concluded that both mini-sternotomy and right anterior thoracotomy, despite longer operative times, provide similar short term outcomes compared to full sternotomy, with reduced hospital LOS [28].…”
Section: Minimally Invasive Cardiac Surgery – Recent Reviews and Meta...mentioning
confidence: 70%
“…In hospital mortality was equivalent between the two groups (MiAVR 1.82% vs FSAVR 3.52%). There were no significant differences in rates of reoperation for bleeding (MiAVR 9.09% vs FSAVR 10.56%), stroke (MiAVR 0% vs FSAVR 1.41%), atrial fibrillation (MiAVR 30.91% vs FSAVR 26.76%), or postoperative blood product usage (MiAVR 41.82% vs FSAVR 42.96%) Both groups had similar ventilation time (MiAVR 9 hours [6][7][8][9][10][11][12][13][14][15][16] Multivariable analysis of operative approach as a risk factor is shown in table 4. There were no differences between the two approaches in MACE (including in-hospital death, stroke, myocardial infraction (MI) and reoperation), sternal wound infection, significant PPM after surgery, readmission during 8 weeks after surgery, perioperative blood products usage and in hospital stay longer than 7 days.…”
Section: Accepted Manuscriptmentioning
confidence: 88%
“…An analysis of the Society of Thoracic Surgeons database made by Ghoreishi et al [5] showed similar mortality rates of 1.9% in both FSAVR, MiAVR via upper hemisternotomy and MiAVR via right thoracotomy. Ogami et al [6] preformed This article is protected by copyright. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With thoughtful effort to curtail unnecessary surgical injury, minimally invasive techniques have gained favor in cardiac surgery, eventually propelling the popularization of minimally invasive approaches for valve operations. 11 , 12 , 13 Although studies on postoperative outcomes have been conducted on isolated valve surgeries, 14 , 15 , 16 , 17 , 18 minimally invasive valve operations have not been compared to open approaches comprehensively to include various valve types within 1 investigation. Furthermore, minimally invasive approaches to valve operations have not been compared to their full sternotomy (FS) counterparts in the context of patient resource utilization.…”
mentioning
confidence: 99%